BRANDERPRENEURSHIP: KEWIRAUSAHAAN BERBASIS PENGEMBANGAN MEREK - Wijaya, Bambang Sukma (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
This article elaborates on a strategic concept for entrepreneurs that allows their business to grow faster by synergizing the entrepreneurial spirit and the branding mindset. Indeed, many entrepreneurs still consider brand development or branding as a 'luxurious strategy' that is wasting money. However, by using the concepts and strategies that are smarter and focused, branding activities can be executed more effectively and efficiently to produce the optimum effect on business performance. Branderpreneurship concept refers to the stages as set out in the ‘circle of values development’: starting from Identifying values, Creating values, Delivering values, Communicating values, Maintaining values, Evaluating values to Updating values. Branderpreneurship concept is beneficial for novice entrepreneurs, start-up businesses, and SMEs that are developing their business. Thus, the public can more quickly recognize their business brand, grows strategically, which would have an impact on increasing business profits.